Institutional aspects of sanitary and phytosanitary issues in ECOWAS trade - Hughes, J.; Bandyopadhyay, Ranajit; Makinde, K.; Olembo, S. (2008)
The Economic Community of West African States (ECOWAS) has accepted trade liberalization and globalization as important policy directions. West African trade with Europe and the United States is already much greater than trade with other developed countries or intra-regional trade, although trading with developed countries may entail considerable difficulties due to trade regulations and the need to conform to Sanitary and Phytosanitary (SPS) standards. There is generally a low level of awareness of quality standards among produce exporters in West Africa. SPS focal points are not established in all countries, which makes it difficult for exporters to check on standards and requirements. Frequent changes to standards, excessive procedural requirements, high costs for testing and certification, and a lack of transparency in the application of standards combine to compromise the ability of many countries to comply effectively with SPS. Many West African countries have not upgraded their national SPS systems in response to the introduction of the SPS Agreement, leading to differences between local and international standards that makes meeting standards difficult for firms that do business in multiple markets. There also is insufficient testing capability to meet the needs for international trade and a lack of regional coordination. Standards application is not enforced in a number of countries, but others have set up institutions for testing, certification, and quality control of both domestic products and imported goods. The effectiveness of these agencies often is weak due to inadequate equipment, a dearth of skilled technical personnel, inability to assess risks, inadequate laboratory accreditation, and a lack of enforcement.